The Comparability of U.S. and EU Unemployment Rates - Kropienė, Rūta (Ekonomika, 2003)
Unemployment indicators in a two world’s largest economies play a very important role for policymakers, researches and the market participants. During the last decade substantial progress has been made in the area of harmonizing of the unemployment indicators in the EU and the US, however some methodological differences still remain making the unemployment levels not fully comparable. The purpose of this article is to review the progress made in area of harmonization and identify how the remaining methodological differences affect the official levels of unemployment Based on the data of the year 2000 unemployment surveys in the US and the EU author comes to a conclusion that the differences are minor, but not negligible. If calculated on the base of the US conception the EU unemployment levels would be lower by 0.1–0.7 percentage points for a different countries and by 0.4 percentage points for the whole EU area. This indicates that further progress in the area of harmonization would be beneficial for a greater comparability of unemployment level indicators. As of today some adjustments could be helpful for a better data comparability.